Ultrasound examination of the salivary glands in Sjogren’s disease - A. V. Torgashina (Научно-практическая ревматология)
The article discusses the importance of ultrasound examination of the salivary glands in Sjogren’s disease for the diagnosis, as well as for assessing the activity of the disease. The characteristics of the main ultrasound changes in the salivary glands and the pathogenetic reasons of these changes are given. The results of studies of the dynamics of changes in ultrasound parameters both in patients not receiving treatment and in the presence of various methods of therapy are presented. The paper also provides basic data on the role of ultrasound in the differential diagnosis of diseases involving the salivary glands.